Learners' Satisfaction in Two Foreign Language Teacher Education Programs: Are We Doing Our Homework? - Gabriel Vicente Obando Guerrero; Ana Clara Sánchez Solarte (Asociación Colombiana de Profesores de Ingles, 2018)
This article reports the results of a descriptive research project whose goal was to identify the degree of satisfaction of students enrolled in two teacher education programs at a public Colombian university. As satisfaction and quality are prevalent terms in curriculum evaluation, and are encouraged by accreditation and government regulations, learner feedback can be valuable input in these processes. Seventy students of beginner, intermediate, and advanced levels from two programs were surveyed. The findings suggest that besides the mechanisms proposed by the government to collect information, student feedback needs to be considered. Regarding the programs, learners display an overall satisfaction, but methodology and assessment need to be considered in future curriculum development and evaluation processes.